2019
DOI: 10.3390/polym11121965
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of the Solution-Processable and Highly Conductive Polyaniline Composites for Optical and Electrochemical Applications

Abstract: Solution-processable conducting polymers (CPs) are an effective means for producing thin-film electrodes with tunable thickness, and excellent electrical, electrochemical, and optical properties. Especially, solution-processable polyaniline (PANI) composites have drawn a great deal of interest due to of their ease of film-forming, high conductivity up to 103 S/cm, excellent redox behaviors, processability, and scalability. In this review, basic principles, fabrication methods, and applications of solution-proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 73 publications
(292 reference statements)
0
20
0
Order By: Relevance
“…The morphology of PCL-PANI mats was characterized and compared to PCL mats ( Figure 2 ). The presence of PANI increased the solution conductivity and the charge density [ 57 , 58 ], causing two main changes in morphology of fibers: (i) the reduction in the average diameter of the fibers, caused by the electrical force that elongates the jet [ 33 ]; (ii) the formation of much thinner “spider-like” fibers, generated by the secondary jets [ 46 ]. FTIR spectra ( Figure 3 ) demonstrated the incorporation of PANI, by displaying both characteristic groups of PCL and PANI-CSA on the PCL-PANI mats.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of PCL-PANI mats was characterized and compared to PCL mats ( Figure 2 ). The presence of PANI increased the solution conductivity and the charge density [ 57 , 58 ], causing two main changes in morphology of fibers: (i) the reduction in the average diameter of the fibers, caused by the electrical force that elongates the jet [ 33 ]; (ii) the formation of much thinner “spider-like” fibers, generated by the secondary jets [ 46 ]. FTIR spectra ( Figure 3 ) demonstrated the incorporation of PANI, by displaying both characteristic groups of PCL and PANI-CSA on the PCL-PANI mats.…”
Section: Discussionmentioning
confidence: 99%
“…Polyaniline (PANI) is one of the most studied conducting polymers. It has a wide range of applications, including wastewater processing [1,2], catalysis [2], sensing [3][4][5][6], biomedical [5,7,8], optical [9] and electrochemical [9][10][11][12][13] applications. Many of these areas require PANI in the form of a thin film.…”
Section: Introductionmentioning
confidence: 99%
“…As observed, the MC absorption peak has increased with the addition of PANI. The two peaks of MC and PANI has also overlapped as a result of the blending process [18]. After the addition of AgNPs, a new adsorption peak characteristic for the surface plasmon resonance (SPR ) of the electrons of AgNPs is observed [19].…”
Section: Optical Properties Of the Synthesized Filmsmentioning
confidence: 99%
“…These results confirmed that the formed films have become more convenient to high rapid optoelectronic devices. The optical conductivity (σopt) which demonstrates the electrical conductivity that produced as a result of the charge carrier's transfer due to the variation in the electric field of the fallen electromagnetic waves has been determined from absorption coefficient ( ) using equation (18) [48]:…”
mentioning
confidence: 99%